Axillary Coverage by Whole Breast Irradiation in 1 to 2 Positive Sentinel Lymph Nodes in Breast Cancer Patients. Issue 4 (July 2016) - De Santis, Maria Carmen; Bonfantini, Francesca; Dispinzieri, Michela; Meroni, Silvia; Diletto, Barbara; Mantero, Elisa D.; Franceschini, Marzia; Soncini, Fulvia; Di Cosimo, Serena; Cosentino, Vito; Pignoli, Emanuele; Lozza, Laura
Purpose: To evaluate the dosimetric coverage of axillary levels I, II, and III obtained with standard whole breast irradiation in 1 to 2 positive sentinel lymph nodes (SLNs) patients not submitted to axillary lymph nodes dissection (ALND), and to compare the lymph nodes areas coverage obtained with 3D conformal radiation therapy, intensity-modulated radiotherapy (IMRT), and volumetric modulated arc therapy (VMAT). Methods: Patients with 1 to 2 positive SLNs undergoing breast-conserving therapy, without ALND, were included in the analysis. For each patient, 3 treatment plans were performed: a 3D conventional tangential plan, a static IMRT plan, and a volumetric IMRT, designed to encompass the entire breast parenchyma. The volumes of axillary levels I, II, and III receiving 90% and 95% (V90, V95) of the whole breast prescribed dose were evaluated. Dose-volume histograms were compared by means of the Friedman test. Results: Ten patients were enrolled. All defined breast volumes received >95% of the prescribed dose with the 3 techniques. Median V95 for axillary level I was 26.4% (range 4.7%-61.3%) for 3D plans, 8.6% (range 0.64%-19.1%) for static IMRT plans, and 2.6% (range 0.4%-4.7%) for volumetric IMRT plans (p<0.001). Median V95 for axillary level II was 5.4% (range 0%-14.6%), 1.9% (range 0%-15%), and 2.6% (range 0.4%-4.7%) for 3D, static IMRT, and volumetric IMRT, respectively (p<0.001). Conclusions: Results of our analysis showed that standard 3D tangential whole breast irradiation failed to deliver a therapeutic dose to axillary levels I and II. The coverage was even lower using static and volumetric IMRT techniques.